CD40 ligand in coronary heart disease patients with Type 2 diabetes mellitus - O. P. Shevchenko; O. F. Prirodova; O. V. Orlova; A. O. Shevchenko (Российский кардиологический журнал, 2006)
The levels of soluble CD40L (sCD40L) and other inflammatory and thrombotic markers were studied in coronary heart disease (CHD)) patients with or without Type 2 diabetes mellitus (DM-2). In total, 56 patients with various CHD forms, as well as 10 healthy volunteers, were examined. In 12 patients, CD-2 was diagnosed. In all participants, the levels of high-sensitive С-reactive protein (hsCRP), fibrinogen, tumor necrosis factor-alpha (TNO-alpha), pregnancy-associated plasma protein A (PAPP-A), soluble vascular cell adhesion molecule-1 (s VCAM-1), and sCD40I were measured. Inpatients with CHD and DM-2 (Group I, n = 12), sCD40I levels were significantly higher than in CHD patients without DM-2 (Group II, n = 44), or control group: 3,07 ± 2,03, 1,72 ± 1,54, and 1,05 ± 1,07 ng/ml, respectively (p < 0, 05). Other marker levels were similar in Groups land II There was no significant sCD40I level difference among subgroups with various CHD forms. Among other cardiovascular risk factors, sCD40L levels correlated significantly with plasma triglyceride levels (p = 0,028; r = -0,301). CHD patients with DM-2 demonstrated significantly higher sCD40L plasma levels, in comparison with diabetes-free CHD patients or healthy individuals, regardless of CHD form or main cardiovascular risk factors.